Plastic and Orthopaedic Interventions and Long-Term Sequelae in Children with Meningococcal Septicemia—40 Years of Experience at the University Children's Hospital Zurich - Elrod, Julia; Mannhard, Doris; Mohr, Christoph; Lienert, Christine; Hagemann-Gysling, Kerstin; Schiestl, Clemens; Mazzone, Luca (European Journal of Pediatric Surgery, 2019)
Introduction Meningococcal septicemia is not merely an acute disease with a high lethality, but patients surviving the fulminant phase can suffer from serious long-term sequelae.Materials and Methods The records of 165 patients admitted to the hospital from 1968 to 2008 with the diagnosis of meningococcal septicemia were retrospectively reviewed for early signs at presentation, intensive care management, acute symptoms, the necessity of plastic and orthopaedic surgical management, and long-term orthopaedic sequelae. Possible predictors of these conditions were determined.Results Overall lethality was 17.5%, and mean time of hospitalization time was 28 days. Integument involvement occurred in 45%, often resulting in the necessity of plastic surgical procedures. Young age is a significant indicator or skin involvement. Amputations were necessary in 9% of all cases, affecting the lower extremities more often than the upper extremities. Six percent of all children suffered from long-term orthopaedic sequelae, such as growth retardation and angular deformities, appearing up to 11 years (mean 4.9 years) after onset of the acute disease. The incidence of amputations and long-term orthopaedic sequelae correlated significantly with severity of the disease.Conclusion Meningococcal septicemia can entail devastating long-term consequences in children surviving the acute phase of the disease. Sequelae may become apparent only years later and cause further damage. To prevent this, a systematic follow-up till adulthood is necessary.
Keywords: amputation; plastic; orthopaedic; adrenal gland failure; meningococcal septicemia